Race, American literature and transnational modernisms - Patterson, Anita Haya (Cambridge studies in American literature and culture, 2008)
Modernist poetry crosses racial and national boundaries. The emergence of poetic modernism in the Americas was profoundly shaped by transatlantic contexts of empire-building and migration. In this ambitious book, Anita Patterson examines cross-currents of influence among a range of American, African American and Caribbean authors. Works by Whitman, Poe, Eliot, Pound and their avant-garde contemporaries served as a heritage for black poets in the US and elsewhere in the New World. In tracing these connections, Patterson argues for a renewed focus on intercultural and transnational dialogue in modernist studies. This bold and imaginative work of transnational literary and historical criticism sets canonical American figures in fascinating contexts and opens up readings of Langston Hughes, Derek Walcott, and Aime Cesaire. This book will be of interest to scholars of American and African American literature, modernism, postcolonial studies, and Caribbean literature.